A validated surrogate analyte LC–MS/MS assay for quantitation of endogenous kynurenine and tryptophan in human plasma. (24th August 2018) - Miller, Dennis; Tan, Lei; Dorshorst, Drew; Morrissey, Kari; Mahrus, Sami; Milanowski, Dennis; McKnight, Janine; Cape, Stephanie; Dean, Brian; Liang, Xiaorong
Aim: Indoleamine 2, 3-dioxygenase (IDO) and tryptophan 2, 3-dioxygenase (TDO) catalyze the initial and rate-controlling step of tryptophan metabolism through the kynurenine pathway, which plays an important role in mediating immune response. Accurate measurement of tryptophan and kynurenine is critical for monitoring the activity of IDO/TDO. Experimental: Surrogate analytes ([15N2]-Tryptophan and [13C6]-Kynurenine) were used for preparation of calibration standard and quality control. A fit-for-purpose validation using an approach of surrogate analyte and authentic matrix was carried out.Results: Acid precipitation was used in sample preparation, which yielded good recovery without significant matrix effect. Precision and accuracy results were well within the acceptance criteria. The assay demonstrated successful application to a clinical study to confirm a transient depletion of kynurenine upon IDO inhibition.Conclusion: A robust, specific and simple LC–MS/MS method was developed and validated with a fit-for-purpose style for measuring tryptophan and kynurenine in human plasma samples.